Comparison between mini-percutaneous nephrolithotomy and retrograde intra renal surgery for the management of lower calyceal calculi of size less than 1.5 cm : Our institutional experience - Jayaprakash Narashimman; Pugazhenthi Periasamy; Mahendran Ganesamoorthy; Thiruvarul PV; Kiran Ramapurath (Asian Journal of Medical Sciences, 2024)
Background: The treatment of lower calyceal calculi with a size <1.5 cm remains a subject of debate. Mini-percutaneous nephrolithotomy (Mini PCNL) and retrograde intrarenal surgery (RIRS) are both effective options, but there is a need for comparative analysis to determine the optimal approach. Mini-perc has the advantage of direct visualization and efficient fragmentation and clearance, while RIRS is a minimally invasive technique with excellent visualization and minimal morbidity. Aims and Objectives: This study aims to evaluate and compare the efficacy, safety, and outcomes of mini-perc PCNL and RIRS in the management of lower calyceal calculi. Materials and Methods: This retrospective comparative cohort study included a total of 72 patients with lower calyceal calculi <1.5 cm. Thirty-six patients underwent mini-perc, and 36 patients underwent RIRS. Results: No significant differences were observed in patient demographic characteristics, stone size, or stone location between the mini-perc and RIRS groups. The mini-perc group had a significantly higher stone-free rate (SFR) (94.4%) compared to the RIRS group (86.1%) (P<0.05). The mini-perc technique had a higher success rate in first-session stone clearance (88.9%) compared to RIRS (77.8%) (P<0.05). The mini-perc group had a longer operative time, higher estimated blood loss, and a longer post-operative hospital stay compared to the RIRS group (P<0.05). Conclusion: Both mini-perc and RIRS techniques are effective for managing lower calyceal calculi <1.5 cm. Mini-perc offers a SFR and a better success rate in first-session stone clearance compared to RIRS. However, mini-perc procedures are associated with longer operative time, higher estimated blood loss, and a longer post-operative hospital stay.